Mixing, mass transfer and energy analysis across bioreactor types in microalgal cultivation and lipid production - Jones, Sarah Melissa Jane (Centre for Bioprocess Engineering Research, 2016)
Microalgae are recognised as a source of lipids for bioenergy, nutrients and pharmaceuticals. Photobioreactors, closed vessels for microalgal cultivation, are known to have high energy consumption due to mixing and aeration. Sparging is commonly used for mixing and gas-liquid mass transfer in photobioreactors, but is energy intensive. The aim of this work was to reduce these energy requirements by optimising conventional sparging and considering surface aeration coupled with mechanical agitation as an alternative. An airlift photobioreactor was used as a base for comparison with two novel, surface aerated reactors: oscillatory baffled and wave photobioreactors. The three bioreactors were compared in terms of power input, mixing, CO2 mass transfer, algal growth and lipid production. Prior to comparison, each photobioreactor was optimised based on these parameters. To calculate power input, isothermal gas expansion equations were used for sparged systems and calorimetry was used for mechanically agitation systems. Mixing was investigated using a salt tracer and phenolphthalein indicator and mass transfer was measured using the gassing-in method. Scenedesmus sp., a high lipid-producer, was cultivated in low nitrate media across a range of mixing rates in each photobioreactor.In the airlift photobioreactor a critical minimum CO2 supply rate (of 2.7×10-5 m s-1) was found, below which carbon was limiting and above which energy was spent on sparging without increased productivity (0.20 g L-1 d-1 biomass; 0.03 g L-1 d-1 lipid). In the oscillatory baffled reactor, insufficient mass transfer limited algal productivity (0.11 g L-1 d-1 biomass; 0.02 g L-1 d-1 lipid). The wave reactor had high CO2 mass transfer coefficients (10 – 140 h-1) in comparison to the airlift (2.7 – 40 h-1) and oscillatory baffled reactors (6.3 – 37 h-1). Sufficient biomass productivity (0.18 g L- -1 d-1) and higher lipid productivity (0.045 g L-1 d-1) at lower power input in the wave reactor resulted in higher energy efficiency compared to the airlift reactor. Life cycle analysis of simulated algal biodiesel production showed that bioreactor energy contributed 99% of total energy consumption. Therefore, the global warming potential was reduced by 73% when the airlift reactor was operated at the critical minimum CO2 supply (with gas compression to 2 bar) and a further 19% when the wave reactor was used. This work offers an energy efficient alternative to sparging, through the generation of a well-mixed wave in a surface aerated bioreactor. It also offers methods for optimisation of energy usage with respect to mixing and aeration. Reducing bioreactor energy consumption is key to feasibility, and was demonstrated here to reduce energy-related environmental burdens.